Russia-Ukraine war and Nigeria’s economy: Mainstreaming nuances of interdependence as integral part of economic development - Ezirim , Gerald; Osuagwu, Christian Onyemaechi (Journal of Contemporary International Relations and Diplomacy, 2026)
This study examined the economic consequences of Russia-Ukraine war on Nigeria’s economy. Russia and Ukraine occupy central positions globally in the power play equation between the major resource-supplier nations and import-dependent ones. The study is anchored on the complex interdependence theory in order to unravel interrelations. It relied on the ex-post facto research design. Documentary method was employed in which case secondary data are sourced from books, journals, official documents, and online sources. Also, content analysis was applied in the study. Findings in the study are that: growth rates in critical sectors such as agriculture, industry, and services of the Nigerian economy have slowed down drastically as a result of the Russia-Ukraine war; Russia-Ukraine war has negatively impacted Nigeria’s oil production measured in (MBPD) from 2022 to 2024; and the wheat market in Nigeria has also been hit by increasing prices as a result of the war; Nigeria’s cumulative GDP growth rate has equally slowed down significantly since 2022. Recommendations are as follows; first, agriculture should be encouraged at all levels of government by prioritizing production rather than import; second, increased local participation in crude production and refining should be encouraged such as what Dangote refinery has come to represent, export of crude and import of refined products should be jettisoned; third, alternatives such as commercial production of cassava flour should be prioritized by government to discourage reliance on imported wheat; fourth, import dependent economies mostly manifest unfavourable GDP growth, hence government should embrace production in all sectors of the economy rather than consumption